Pengajaran PKn di sekolah dasar Model Gallery Walk dalam pembelajaran PPKN : Peningkatan Prestasi Belajar Peserta Didik dengan Menggunakan Model Gallery Walk dalam pembelajaran PPKN di Kelas V SDN 02 Serang - Kurneasih, Yanti (Amal Insani Foundation, 2024)
This study investigates how the application of the Gallery Walk model in Class V SDN 02 Serang to improve student learning outcomes in the subject of Pancasila and Citizenship Education (PPKn). The purpose of this study is to find out how effective the Gallery Walk method is in increasing students' active participation and understanding of the material. This study collects data through classroom action research with a qualitative descriptive approach, which includes interviews, observations, and learning outcome tests. The results showed that the students' scores increased significantly from 65 on the initial test to 90 after the application method. This research helps develop an interactive and participatory learning approach in primary schools and provides educators with an understanding of how Gallery Walk functions in PPKn.